Comparison of visual and instrumental assessment of colour differences on finished wooden surfaces : Usporedba vizualne procjene i izmjerene promjene boje površinski obrađenog drva - Pavlič, Matjaž (Array, 2020)
Staining of wood with various substances and processes is an important part of surface finishing of wood. Colour differences as a result of staining and of exposure of coloured wood during its utilisation are usually evaluated by instrumental measurements. However, the measurement results can show something else compared to what our naked eye can see. Due to inhomogeneity of wood, this discrepancy can be even greater in the case of finished surfaces. The aim of our research was to evaluate distinctions between visual perception and numerically determined colour differences on differently finished wooden surfaces, to get information at which starting point the colour difference becomes visible, and to establish whether it is related to the nature of the surface. We established that the visual assessment is influenced by many factors and that there is a correlation between visual and instrumental assessments. The colour difference ΔE* of 0.5 should be considered as a value when it starts to become visible, and at the value of 2.0, observers already considered the colour difference as a different colour. It was stated that we have some tolerance in perceiving the colour change. This tolerance is more expressed in the case of transparent coating systems.